2015
DOI: 10.1038/emm.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Klebsiella pneumoniae-derived extracellular vesicles protects against bacteria-induced lethality via both humoral and cellular immunity

Abstract: The emergence of multidrug-resistant Klebsiella pneumoniae highlights the need to develop preventive measures to ameliorate Klebsiella infections. Bacteria-derived extracellular vesicles (EVs) are spherical nanometer-sized proteolipids enriched with outer membrane proteins. Gram-negative bacteria-derived EVs have gained interest for use as nonliving complex vaccines. In the present study, we evaluated whether K. pneumoniae-derived EVs confer protection against bacteria-induced lethality. K. pneumoniae-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 50 publications
10
97
0
1
Order By: Relevance
“…The macrophage responses to these OMVs were distinctly more potent than to purified outer membrane and demonstrate that porin composition is a key determinant of the intensity of inflammatory cytokine production. It has recently been demonstrated that vaccination with OMVs from Klebsiella pneumoniae is capable of generating an effective protective response (61). However, this new study does not consider the impact of alterations to OMV composition such as those exhibited with porin loss.…”
Section: Figmentioning
confidence: 95%
“…The macrophage responses to these OMVs were distinctly more potent than to purified outer membrane and demonstrate that porin composition is a key determinant of the intensity of inflammatory cytokine production. It has recently been demonstrated that vaccination with OMVs from Klebsiella pneumoniae is capable of generating an effective protective response (61). However, this new study does not consider the impact of alterations to OMV composition such as those exhibited with porin loss.…”
Section: Figmentioning
confidence: 95%
“…However, when analyzing the proliferation of the bacteria in the scenario of absence of Factor B, the lack of activation of the classical pathway of the complement system seemed to support the bacterial proliferation almost exponentially, this result as also observed in a C5 depletion setup (Nypaver et al, 2010). Additionally, the intraperitoneal adoptive transference of the sera of mice immunized with extracellular vesicles of K. pneumoniae, led to protection from the lethality induced by the intraperitoneal challenge of a high dose of K. pneumoniae (Lee et al, 2015). Taken together, these results suggests that even though some strains of K. pneumoniae possesses resistant mechanisms against the complement system, it activation plays a major role in K. pneumoniae infection control.…”
Section: Resultsmentioning
confidence: 77%
“…We did not assess the differentiation of naĂŻve lymphocytes in Th17 cells. However, other studies have shown that there are ways to achieve protection against K. pneumoniae in a non-IL17 dependent manner (Tsao et al, 2015;Lee et al, 2015). The activation of the complement system pathways lead to the fragmentation of C5, thus the production of the fragment C5a, a potent neutrophil chemoattractant (Mayadas, Cullere et Lowell, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above indicates that parts of NVs from tumor cells or pathogens are able to provide protective capability against immunity-requiring diseases [32]. Thus, vesicle-based vaccines are promising way to cope with diseases derived from vesicle-generating-cells.…”
Section: Vaccine Developmentmentioning
confidence: 99%